Palladium-catalyzed stereoselective C-glycosylation of glycals with sodium arylsulfinates - Ma, Jimei (2015)
An efficient glycosylation method to synthesize 2-deoxy-C-aryl glycosides was developed. This C-glycosylation strategy is based on a palladium-catalyzed desulfitative Ferrier-type coupling reaction of glycals and sodium arylsulfinates. A series of C-aryl glycosides were obtained in moderate to good yields with exclusive regio- and stereoselectivities. The anomeric selectivity was found to depend on the configuration of the C3 substituent of the glycals.